OCCURRENCE OF JUVENILES OF THE INDIAN MACKEREL RASTRELLIGER KANAGURTA (CUVIER) IN BOMBAY WATERS - Pillai, S Krishna; Jayaprakash, A A (Indian Journal of Fisheries, 2011)
Juveniles of the Indian mackerel, Rastrelliger kanagurta (Cuvier) 86-142 mmsize are recorded for tine-, fot /ti'rhe. from Bombay waters. Their occurrence offBombay appears to be Jsi3:lated..The, food •of thesd yOung mackerel consisted mainlyof planktonic organisms like Coscinodiscus and copepods